(untitled) (Khairulummah, 2023)
Context Theory is an important chapter of Semantic studies. It deals with the context and circumstances around a textual speech or oral conversation. It includes all related factors that can affect the meanings of that text or conversation. It has two main streams: Linguistic context which emphasize language tools whereas non-linguistic context which discusses circumstances. When we come over to this theory we now better that any conversations or text could not be understood without knowing the context either it is linguistic or non-linguistic. This article studies the non-linguistic context and its effect on fixing the meanings in sayings of Prophet (PBUH). It will attract the potential researchers to make their research in this very important aspect of semantic studies especially related to the sayings of our beloved Prophet Muhammad (PBHU). Interestingly Muslim scholars who had wrote Quranic Tafseer and Explanations of Sayings of Prophet (PBUH) never ignored the contextual meanings whereas context Theory has been presented by European Linguistics but the concept was in minds of Muslim scholars. The article will take the analysis of Imam Subki who wrote the explanation of “Sunan Abi Daoud” and discussed the context theory with all its components. This is an example of a vast research in the field of Context Theory.